2017
DOI: 10.1021/acs.langmuir.7b02098
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and/or pH-Responsive Surfaces with Controllable Wettability: From Parahydrophobicity to Superhydrophilicity

Abstract: Multifunctional surfaces with reversible wetting characteristics are fabricated utilizing end-anchored polymer chains on hierarchically roughened surfaces. Temperature- and/or pH-responsive surfaces are developed that exhibit reversible and controllable wettability, from the "parahydrophobic" behavior of natural plant leaves all the way to superhydrophilic properties in response to the external stimuli. For this purpose, dual scale micro/nanoroughened surfaces were prepared by laser irradiation of inorganic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 79 publications
(143 reference statements)
0
19
0
Order By: Relevance
“…However, with enough long heating process, the reduction of water would definitely happen. Due to the flexible tunability of temperature responsive materials, temperature E‐LIS with reversibly adjustable wettability have become a hot topic research . In 2013, Yao et al first developed a temperature E‐LIS based on n‐paraffin infused organogel, as shown in Figure a.…”
Section: Design and Fabrication Of E‐lismentioning
confidence: 99%
“…However, with enough long heating process, the reduction of water would definitely happen. Due to the flexible tunability of temperature responsive materials, temperature E‐LIS with reversibly adjustable wettability have become a hot topic research . In 2013, Yao et al first developed a temperature E‐LIS based on n‐paraffin infused organogel, as shown in Figure a.…”
Section: Design and Fabrication Of E‐lismentioning
confidence: 99%
“…In addition to thermoresponsive polymers, which have been used extensively to fabricate the thermoresponsive surfaces, thermoresponsive inorganic oxides can also be used to get reversible thermoresponsive wetting transition [37,38]. Due to the fast switching wettability in a narrow temperature range, thermoresponsive surfaces offer promising applications in areas including the thermally driven movement of liquid, oil-water separation, and switchable adhesion on the surface [39][40][41][42][43][44].…”
Section: Temperature-responsive Surfacesmentioning
confidence: 99%
“…In this paper, an open flow reactor (OFR) with wetting contrast has been successfully manufactured by direct laser sintering. [ 16 ] Laser sintering is an emerging technology for designing patterns on the surface of various materials such as plastic, metal, glass, ceramic, and wood. It is a mask‐less process and can write arbitrary geometric figures directly.…”
Section: Introductionmentioning
confidence: 99%